Power system control and stability - Anderson, P. M. (Paul M.) (IEEE Press power systems engineering series., 1994)
Analyzes the dynamic performance of interconnected power systems. * Examines the characteristics of the various components of a power system during normal operating conditions and during disturbances. * Explores the detailed mathematical models of system components and analyzes the system behavior using the necessary computational tools.